Consumer price index numbers for industrial workers : (2001=100) ; annual report 2017 - India. Ministry of Labour & Employment. Labour Bureau (Delhi: Controller of Publications, 2018)
The Consumer Price Index Numbers for Industrial Workers CPI(IW) are being compiled, maintained and disseminated by the Labour Bureau since its inception in October, 1946. These index numbers are being utilized for fixation and revision of wages and determination of variable Dearness Allowances payable to workers in workers in organized sectors of the economy. Despite the coverage being limited to Industrial Workers, presently, the CPI(IW) are also utilized as an indicator for measuring inflationary trend in the country and for policy formulations.
Includes Annexure I & II
Keywords: Consumer Price Index - India